TOLERANCE OF AUTOCHTHONOUS LACTIC ACID BACTERIA TO DIFFERENT PROCESSING CONDITIONS IN VITRO - Grujović, Mirjana (Food and Feed Research, 2020)
In this paper, the effect of different temperatures, pH, and NaCl concentration on the growth of autochthonous lactic acid bacteria isolated from traditionally made Serbian cheese (Sokobanja area) was investigated by using the spectrophotometric method. Growth of tested Lactobacillus (Lb. fermentum, Lb. plantarum, and Lb. brevis) and Lactococcus lactis subsp. lactis biovar. diacetylactis five isolates were better in acidic pH, while the growth of Enterococcus isolates (E. durans, E. faecium, and E. faecalis) was better in basic pH, at 37 °C. At 4 °C after 24 h, none of the tested bacteria showed growth. Since the autochthonous isolates were tolerant to a tested range of dairy processing conditions, further studies need to include the characterization of enzymatic activity of selected isolates, as well as the ability to use these isolates like starter cultures or food supplements in dairy or non-dairy products.